Iterative Methods for the Numerical Solutions of Boundary Value Problems - Abushammala, Mariam B. H. (2014)
A Master of Science thesis in Mathematics by Mariam B. H. Abushammala entitled, "Iterative Methods for the Numerical Solutions of Boundary Value Problems," submitted in June 2014. Thesis advisor is Dr. Suheil A. Khoury. Available are both hard and soft copies of the thesis.